2008
DOI: 10.1523/jneurosci.2196-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Lrig1 Is an Endogenous Inhibitor of Ret Receptor Tyrosine Kinase Activation, Downstream Signaling, and Biological Responses to GDNF

Abstract: Glial cell line-derived neurotrophic factor (GDNF)/Ret signaling has potent trophic effects on ventral midbrain dopaminergic, motor, sensory, and sympathetic neurons. The molecular mechanisms that restrict Ret receptor tyrosine kinase activation are not well understood. Here, we show that Lrig1, a transmembrane protein containing leucine-rich repeats and Ig-like domains in its extracellular region, acts in a negative feedback loop to regulate the activity of Ret receptor tyrosine kinase. In particular, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 53 publications
1
113
1
Order By: Relevance
“…For example, MET signalling is inhibited by both LRIG1 (Shattuck et al, 2007) and RALT (Pante et al, 2005). LRIG1 is also capable of suppressing RET signalling (Ledda et al, 2008). These data are interesting in light of the fact that functional and/or physical interactions between MET and ErbB RTKs (Jo et al, 2000;Scheving et al, 2002;Engelman et al, 2007), as well as between RET and the EGFR (Croyle et al, 2008), have been reported.…”
Section: Socs4 and Socs5mentioning
confidence: 79%
“…For example, MET signalling is inhibited by both LRIG1 (Shattuck et al, 2007) and RALT (Pante et al, 2005). LRIG1 is also capable of suppressing RET signalling (Ledda et al, 2008). These data are interesting in light of the fact that functional and/or physical interactions between MET and ErbB RTKs (Jo et al, 2000;Scheving et al, 2002;Engelman et al, 2007), as well as between RET and the EGFR (Croyle et al, 2008), have been reported.…”
Section: Socs4 and Socs5mentioning
confidence: 79%
“…MN1 is an immortalized mouse-derived motor neuron cell line expressing Lrig1 that was cultured in DMEM supplemented with 7.5% FBS [24]. BDNF was purchased from R&D Systems (Abingdon, UK) and MG-132 was from Calbiochem.…”
Section: Methodsmentioning
confidence: 99%
“…adhesion molecules or modulating neurotrophic growth factor receptor signaling during neural development [15,24,42]. Working in trans as cell adhesion molecules, many LRR transmembrane proteins affect axonal extension, guidance, target selection, and synapse formation [15,[43][44][45][46].…”
Section: Lrr Transmembrane Proteins and Nervous System Developmentmentioning
confidence: 99%
“…4). Lrig1, a transmembrane protein containing leucine-rich repeats and Ig-like domains, interacts with Ret thereby inhibiting its recruitment to lipid rafts, the binding to the GDNF-GFRa1 complex, receptor autophosphorylation, and MAPK activation in response to GDNF (Ledda et al, 2008). Growth Arrest Specific 1 (Gas1) is a molecule involved in cell cycle arrest and widely expressed during development, but also induced during, and participating in, excitotoxic neuronal death (Mellstrom et al, 2002).…”
Section: Negative Regulation Of Gdnf Expressionmentioning
confidence: 99%